2016
DOI: 10.1136/bcr-2015-212576
|View full text |Cite
|
Sign up to set email alerts
|

Rare gynaecological emergency: massive intraperitoneal haemorrhage from spontaneous rupture of a superficial vessel on a large leiomyoma

Abstract: Uterine leiomyomas rarely present as gynaecological emergencies. We report a case of a 29-year-old nulliparous woman, with a negative pregnancy test, who presented with collapse and an admission haemoglobin count of 68 g/L. Urgent CT of the abdomen revealed a 14 × 19 × 10 cm uterine fibroid and intraperitoneal free fluid. Emergency laparotomy confirmed massive intraperitoneal haemorrhage from a large serosal vessel on top of a 19 cm subserosal fibroid. A myomectomy was performed, preserving this patient's fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Additionally, vessel rupture can be either spontaneous or traumatic. Similar to the current case, reports of spontaneous venous rupture causing hemoperitoneum and hypovolemic shock have been reported [9,13,14]. Schwartz and Powell reported a case of a 53-year-old woman with a known history of uterine leiomyoma with unrelenting acute abdominal pain and a positive FAST exam.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Additionally, vessel rupture can be either spontaneous or traumatic. Similar to the current case, reports of spontaneous venous rupture causing hemoperitoneum and hypovolemic shock have been reported [9,13,14]. Schwartz and Powell reported a case of a 53-year-old woman with a known history of uterine leiomyoma with unrelenting acute abdominal pain and a positive FAST exam.…”
Section: Discussionsupporting
confidence: 78%
“…Spontaneous avulsion of a leiomyoma with active hemorrhaging from the right uterine artery was the perpetrator behind the bleeding [13]. Additionally, Gulati et al performed a fertility-sparing myomectomy in a 29-year-old with hemoperitoneum resulting from spontaneous rupture of a serosal vessel overlying a subserosal leiomyoma [14]. In contrast to spontaneous rupture, cases with specific etiologic agents have also been reported [4].…”
Section: Discussionmentioning
confidence: 99%
“…Akahira et al [24] reported the case of a 44-year-old multiparous woman with hemoperitoneum due to a ruptured artery overlying a uterine leiomyoma, who underwent total abdominal hysterectomy. Gulati et al [25] reported a case of a 29-year-old nulliparous woman with intraperitoneal hemorrhage from a large serosal vessel, who underwent myomectomy in an attempt to preserve the fertility of the patient. Cerruto et al [26] reported a case a 47-year-old woman, with three previous pregnancies, who underwent hysterectomy with ovarian conservation.…”
Section: Discussionmentioning
confidence: 99%
“…Uterine myomas are benign female tumours with an estimated prevalence of 25% 1. Symptoms depend on the location and size of the myomas; some myomas are asymptomatic 2 3. In our case, the uterine myoma was relatively large (14 cm in size), but the patient was asymptomatic.…”
Section: Discussionmentioning
confidence: 60%